Barriers to the use of integrated project delivery (IPD): a quantified model for Malaysia. Issue 1 (22nd July 2019) - Durdyev, Serdar; Hosseini, M. Reza; Martek, Igor; Ismail, Syuhaida; Arashpour, Mehrdad
Abstract : Purpose: The purpose of this paper is to quantify the barriers to the use of integrated project delivery (IPD), as assessed by 115 construction professionals in Malaysia. Design/methodology/approach: Barriers recording highest citation amongst researchers worldwide were collated in the form of a conceptual model. This model was validated via a partial least squares structural equation modelling technique. Findings: Findings advance the body of knowledge on IPD by providing original insights into the nature of key barriers, quantifying the relative importance of each barrier. Research limitations/implications: Despite the above-mentioned contributions, and before drawing any conclusion, it is prudent to acknowledge limitations, particularly the chosen research approach in focusing on the Malaysian context. Therefore, caution must be exercised in direct application of findings to other contexts; research findings should be seen through the lens of moderatum generalisations (see Payne and Williams, 2005 ). Practical implications: Apart from contributions to the body of knowledge, for the world of practice, conditions impacting a transition to IPD are discussed, with a recommendation for change management through a tested mechanism like the European Corporate Sustainability Framework. Originality/value: Being the first empirical study undertaken to quantify the relationship among the identified barriers and IPD, the present study contributes to the field by addressing the gap in IPD research in Malaysia, as an exemplar of a developing country; it creates knowledge to inform further improvements in project performance through facilitating IPD use. The study also offers insight to construction stakeholders in other developing countries for tackling issues that hinder the adoption of an IPD approach, and it also points to major barriers such that resources for tackling barriers may be allocated properly.